Impact of earning management and business strategy on financial distress risk of Vietnamese companies - Quang Luu Thu (Cogent Economics & Finance, 2023)
Many Vietnamese companies' net incomes have increased significantly in recent years as a result of creative competitive strategies, but many of them are being forced to delist due to persistent losses and manipulative earnings. In this paper, we are the first to investigate the simultaneous impact of business strategy and earning management on the risk of financial distress. The sample for the study includes information from 601 companies that are listed on the Ho Chi Minh City Stock Exchange between 2010 and 2021. The finding indicates that there is a high risk of financial distress for companies that manipulate earnings by increasing discretionary accruals value. However, if firms manipulate earnings through real operations, the risk of financial distress is reduced. Firms will see a significant improvement in their financial performance if they adopt a key differentiation or low-cost leadership strategy that gives them a competitive advantage in the same industry. The firm size, leverage, firm loss, and liquidity ratio are also the main factors that influence financial distress risk. These results are robust by using alternative proxies of financial distress risk (O and ZM score) to control for potential endogeneity.
Keywords: 330; Asset Turnover of Operation; business strategy; cost of goods sold; earning management; financial distress; profit margin